Effect of ovarian hormones on early embryonic development - San Martín, M. (2015)
The results point out some effects of the ovaric hormones like substance over the early embryological development. Estrogens show a tendency to decrease the egg segmentation rate and to decrease the mucin coat around the egg. In the other hand, progesterone produces only increase of the mucin coat.